Maintained anxiolytic effects of cannabidiol after treatment discontinuation in healthcare workers during the COVID-19 pandemic - Souza, José Diogo S.; Zuardi, Antonio W.; Guimarães, Francisco S.; Osório, Flávia de Lima; Loureiro, Sonia Regina; Campos, Alline Cristina; Hallak, Jaime E. C.; Dos Santos, Rafael G.; Machado Silveira, Isabella Lara; Pereira-Lima, Karina; Pacheco, Julia Cozar; Ushirohira, Juliana Mayumi; et al. (Frontiers in Pharmacology, 2022)
OBJECTIVE: To assess whether the effects of oral administration of 300mg of Cannabidiol (CBD) for 28 days on mental health are maintained for a period after the medication discontinuation. METHODS: This is a three months follow-up observational and clinical trial study. The data were obtained from two studies performed simultaneously by the same team in the same period and region with Brazilian frontline healthcare workers during the COVID-19 pandemic. Scales to assess emotional symptoms were applied weekly, in the first month, and at weeks eight and 12. RESULTS: The primary outcome was that, compared to the control group, a significant reduction in General Anxiety Disorder-7 Questionnaire (GAD-7) from baseline values was observed in the CBD group on weeks two, four, and eight (Within-Subjects Contrasts, time-group interactions: F1-125= 7.67; p=0.006; ηp2=0.06; F1-125= 6.58; p=0.01; ηp2=0.05; F1-125 = 4.28; p=0.04; ηp2=0.03, respectively) after the end of the treatment. CONCLUSIONS: The anxiolytic effects of CBD in frontline health care professionals during the COVID-19 pandemic were maintained up to one month after the treatment discontinuation, suggesting a persistent decrease in anxiety in this group in the real world. Future double-blind placebo-controlled clinical trials are needed to confirm the present findings and weigh the benefits of CBD therapy against potential undesired or adverse effects.